Kuasa Media Massa dan Problem Identitas - ST TRI GUNTUR NARWAYA (Komunikator, 2013)
As a sign, identity exists and thrives in some relationship aspects, including political environment, economic environment and social environment. In some cases, identity can be a problem, such as identity problems of minority in Indonesia. Throughout human history, identity problems have showed the violence of certain identities. This paper attempts to explore the power of mass media and identity problems by using some critical views of identity, such as Stuart Hall’s view of identity. Keywords: identity, power, mass media